Effects of temperature and metals (zinc and cadmium) in embryonic stage of Anabas testudineus : an alternative freshwater fish embryo test in the Southeast Asia Region - Nurulnadia Mohd Yusoff,; Baharom Mohamad Zahid,; Muhammad Azri Shariff,; Ching, Looi Yong; Najihah Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The fish embryo acute toxicity test (FET) was proposed as a promising alternative to the general practice of fish acute toxicity test (FAT). To date, the available information on freshwater fish embryos in Southeast Asia is limited. Hence, this study aims to present preliminary data on single and combined exposure effects of temperature and metals (zinc and cadmium) on the embryonic development of Anabas testudineus. Over 80% of the embryos died after 10 h post-fertilization (hpf) in 1.59, 7.02, and 13.0 mg/L cadmium treatments, whereas the same effect was only observed in 49.6 and 146 mg/L of zinc treatments as early as 8 hpf. The optimum temperature for embryos ranged from 27 to 34 °C, with a survival rate greater than 90% was recorded. The combined test of zinc + cadmium showed the additive effect with approximately 80% mortality at 12 hpf, while the combination of temperature + cadmium had increased the mortality rate up to 100% at 16 hpf. The constant temperature even at optimum rearing value was found to increase cadmium uptake in the embryos and magnified the concentration higher than in water. Therefore, this study suggests climbing perch (Anabas testudineus) could be an alternative FET test model in this region.